Analisis Efektivitas dan Efisiensi Anggaran Corporate Social Responsibility - Rahma Amalia Hapsari; Zahra Wahyuni Asis (Jurnal Ekonomi & Bisnis, 2023)
Corporate social responsibility is an obligation carried out by companies regulated in article 74 paragraph (1) of Law no. 40 of 2007 concerning Limited Liability Companies. The social responsibility carried out by PT Satria Jaya Sentosa is realized through community development and empowerment programs. The aim of this research is to determine the forms of social responsibility programs managed by PT Satria Jaya Sentosa and to determine the effectiveness and efficiency of the CSR program budget at PT Satria Jaya Sentosa. The method used in this research is descriptive qualitative. Data collection was carried out using observation, interviews and documentation techniques. Data analysis techniques by calculating the level of effectiveness and efficiency of budget realization. The research results show that there are three program areas that are the main focus of CSR at PT Satria Jaya Sentosa, namely in the fields of education, health and economic independence. The effectiveness of the CSR program budget at PT Satria Jaya Sentosa can be concluded that the budget is less effective with an effectiveness level of 70%. Meanwhile, the efficiency of the CSR program budget at PT Satria Jaya Sentosa can be concluded that the results are very efficient with an efficiency level of 8%.